Implications of Basel II for financial stability. Clouds are darker for developing countries - Tonveronachi, Mario (PSL Quarterly Review, 2012)
Placing Basel II in the perspective of the more general trend in financial regulation, the paper analyses its efficacy and efficiency as a device to foster financial resiliency. In assessing the criticisms levelled against the New Accord, special attention is devoted to the case of the emerging countries. I suggest that Basel II is neither a sufficient, nor a necessary condition to attain systemic financial stability, especially in weak institutional and macro-policy environments. Taking also into account just how complex and onerous the scheme is, I conclude that the emerging countries should look for new international institutional arrangements based on the principle of astability level playing field. JEL Codes: G21, G28, O16, P34